Gantung diri (Hanging) - Abdul Karim Lubis; Guntur Bumi Nasution; Mistar Ritonga (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Dead by hanging is very common in the community. This form of suicide is often encountered since it can be done anywhere or anytime and it requires only a piece of rope, a neck tie, or anything that can strangle the neck. Dead is hanging is often caused by asphyxia The most common by encountered sign of asphyxia in the victims are cyanosis, congestion, oedema, petechial haemoorrhage.Keywords: hanging; asphyxia